UPAYA KEMANDIRIAN PESANTREN MELALUI BISNIS: STUDI LITERATUR - Sya'diyah, Cholifatus Sya'diyah; Roviatul Adawiyah; Sukeng Tiyas Sari; Muchammad Fajeril Falaach; Harbatul Ahkam Arrozy; Imelda Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic boarding schools have developed into centers of religious education as well as economic drivers through the establishment of business units. Various types of businesses such as cooperatives, agriculture, plantations, fisheries, manufacturing, and trade are the main means to achieve financial independence, support educational operations, and empower the economy of the surrounding community. Examples of businesses include BMT Sidogiri, Toko Basmalah, weaving crafts, and retail units such as mini markets. The pesantren business units also utilize local resources, business diversification, digital technology, and Islamic economic principles to ensure sustainability.The pesantren business units not only contribute to the economy but also create jobs, train the skills of students and alumni, and improve the welfare of the community. By applying professional management, diversification strategies, and partnerships with external parties, pesantren are able to overcome the challenges of the times while maintaining Islamic principles. This approach makes pesantren a model of innovative and financially independent educational institutions.